PENYULUHAN DAN PEMANFAATAN KULIT BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) KOMBINASI MADU SEBAGAI PELEMBAB BIBIR KERING TERHADAP KETUA KAMAR PUTRI ASRAMA PUSAT PONDOK PESANTREN SLAFIYAH SYAFI'IYAH SUKOREJO - Rini Junaidah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Cosmetics aim to cleanse, change the appearance, and maintain the body. Lips are a more sensitive part of the body than other parts of the skin. Therefore, the selection of ingredients in making lip cosmetics must be considered. The addition of coloring agents can affect appearance and can increase self-confidence. Cosmetic preparations are used to color the lips, with the aim of improving the aesthetics of facial makeup and providing an attractive facial expression. Lip balm is a waxy substance used to prevent dry and chapped lips. Natural dyes from red dragon fruit extract (Hylocereus polyrhizus) can replace the role of synthetic dyes such as rhodamine B, which are often used in cosmetic manufacturing. Honey is a thick, yellow liquid produced by bees from nectar and has many uses depending on the type. Dragon fruit has potential. This fruit is characterized by bright red skin with purplish-red flesh and a sweet, fresh taste. Red dragon fruit is known for its rich nutritional content and health benefits.